2010
DOI: 10.1007/s00726-010-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

S100P: a novel therapeutic target for cancer

Abstract: S100P expression is described in many different cancers, and its expression is associated with drug resistance, metastasis, and poor clinical outcome. S100P is member of the S100 family of small calcium-binding proteins that have been reported to have either intracellular or extracellular functions, or both. Extracellular S100P can bind with the receptor for advanced glycation end products (RAGE) and activate cellular signaling. Through RAGE, S100P has been shown to mediate tumor growth, drug resistance, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 60 publications
2
89
2
1
Order By: Relevance
“…The activation of RAGE by S100P stimulates cellular signaling pathways, including the MAP kinase and NF-κB pathways (19,22,26). Certain studies have indicated that inhibiting S100P-RAGE interactions significantly reduces the basal levels of NF-κB activity in pancreatic cancer and supports the existence of an autocrine loop involving RAGE ligands and RAGE in pancreatic cancer (2,25,26). S100B and S100A6 have been shown not only to interact with distinct RAGE immunoglobulin domains, but also to exert opposite effects on cell survival (27,28).…”
Section: +mentioning
confidence: 95%
See 1 more Smart Citation
“…The activation of RAGE by S100P stimulates cellular signaling pathways, including the MAP kinase and NF-κB pathways (19,22,26). Certain studies have indicated that inhibiting S100P-RAGE interactions significantly reduces the basal levels of NF-κB activity in pancreatic cancer and supports the existence of an autocrine loop involving RAGE ligands and RAGE in pancreatic cancer (2,25,26). S100B and S100A6 have been shown not only to interact with distinct RAGE immunoglobulin domains, but also to exert opposite effects on cell survival (27,28).…”
Section: +mentioning
confidence: 95%
“…More than 95% of patients diagnosed with pancreatic cancer succumb to the disease and half of these patients within six months after diagnosis (2,3). Radio-and chemotherapy do not have major effects on the survival of pancreatic cancer patients (2,4); thus, surgery remains the optimal treatment method. Prognosis mainly depends on early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1B). Table Ⅱ lists the 301 upregulated genes in TNBC, including ubiquitin-conjugating enzyme E2C (UBE2C) (14), S100 calcium binding protein P (S100P) (15), ubiquitin carboxyl-terminal esterase L1 (ubiquitin thiolesterase) (UCHL1) (16), pituitary tumor-transforming 1 (PTTG1) (17), ubiquitinconjugating enzyme E2T (UBE2T) (13), ubiquitin-like with PHD and ring finger domains 1 (UHRF1) (18), SIX homeobox 1 (SIX1) (19), and protein regulator of cytokinesis 1 (PRC1) (20), which were previously reported to be overexpressed in breast cancer and involved in mammary carcinogenesis. In particular, topoisomerase (DNA) Ⅱα (TOP2A) (21,22), HORMA domain containing 1 (HORMAD1) (23), ATPase family, Fatty acid binding protein 5 (psoriasis-associated) (FABP5) (24), and AAA domain containing 2 (ATAD2) (25) were previously reported to be potentially involved in the carcinogenesis of TNBC, and to serve as prognostic markers or therapeutic targets for TNBC.…”
Section: Identification Of Genes Upregulated or Downregulated Inmentioning
confidence: 99%
“…Purified RNA from each clinical sample and cell line, as well as poly-A RNA from normal human heart, lung, liver, and kidney (Takara, Otsu, Japan) was reverse transcribed for single-stranded cDNA using oligo(dT) [12][13][14][15][16][17][18] primers with Superscript II reverse transcriptase (Invitrogen, Life Technologies, Carlsbad, CA, USA). qRT-PCR analysis was performed using an ABI PRISM 7500 Real-Time PCR system (Applied Biosystems, Life Technologies, Carlsbad, CA, USA) and SYBR Premix Ex Taq (Takara) according to the manufacturer's instructions.…”
Section: Quantitative Reverse Transcription-pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…Two further review articles deal with the role of S100P in tumorigenesis (Gibadulinova et al 2010;Arumugam and Logsdon 2010). By focusing on transcriptional regulation of S100P in cancer, the first article discusses recent studies that implicate, besides DNA hypomethylation, bone morphogenic protein and non-steroidal anti-inflammatory drugs in the control of S100P expression during tumor progression.…”
mentioning
confidence: 99%